Automatic Flight Control System Design of Level Change Mode for a Large Aircraft. (5th February 2013) - Gong, Huajun; Zhen, Ziyang; Li, Xin; Jiang, Ju; Wang, Xinhua
The level change mode is an essential part of large civil aircraft automatic flight control systems. In cruise, with the decrease of the plane's weight caused by fuel consumption and the influence of bad weather, such as thunderstorms, the level change mode is required to solve this problem. This work establishes a nonlinear model of large aircraft, takes level changed from 9500m to 10100m as an example to design control laws for the level change mode in cruise. The classical engineering method is used to design longitudinal and lateral control laws synthetically. The flight qualities are considered in the design process. Simulation results indicate the control laws can meet design requirements and have a good anti-gust performance.